Network games: The optimal network contract and the efficiency of bypass in oligopolistic network industries under light regulation - Burnell, Stephen; Evans, Lewis; Yao, Shuntian (School of Management Working Papers, 1995)
This paper considers the performance of a market in which a network supplies retail firms with an essential input. There is imperfect competition in the retail market. The regulatory environment is one of light-handed regulation in which the same network contract must be offered to each retail firm. The optimal contract from the perspective of the network is characterised for Nash equilibria in three cases: where the network operates as a separate firm, where it operates as a conglomerate with devolved decision making to its retail division and where a conglomerate structure fully integrates the network and a retail firm. Because of a key characteristic of networks, it is shown that, given the possibility of bypass, unfettered oligopolistic competition under light handed regulation will generally be approximately efficient. These results are placed in the context of the literature concerned with regulating network industries.